Development of Cortical GABAergic Innervation - Thomson, Alex M.; Jovanovic, Jasmina N. (Frontiers in Cellular Neuroscience, 2011)
The mature neocortex contains many different classes of GABAergic inhibitory interneurones, distributed, with some degree of selectivity, through six layers and through many different regions. Some of the events in the early lives of these neurones that may determine their ultimate destination, their maturation and their selective innervation of targets appropriate for each subtype, are discussed. Both time and place of birth influence the class of interneurone that an early post-mitotic interneuronal precursor will become, driven by the selective expression of different combinations of transcription factors in different regions of their birth-places in the ganglionic eminence and ventricular zone. The long distance migration of these precursors along tangential routes in marginal, subventricular and intermediate zones and their final radial movement, into the developing cortex, is regulated by chemical cues, both attractant and repellent. Once they arrive at their final destination, they must integrate into the developing circuitry. As they mature within the cortex, their axons grow and branch in highly specific patterns that may be partially determined by the genetic blueprint for each interneuronal class and partly by the environment in which they find themselves. Finally, as each interneurone class begins to form synapses with only certain postsynaptic targets, cell-cell recognition, most probably via protein-protein interactions across the synaptic cleft, facilitate the formation of appropriate synapses.